VIGILÂNCIA SANITÁRIA DE ALIMENTOS: UMA PROPOSTA PARA ANÁLISE DE CONTEXTOS LOCAIS - Busnello, Maristela B.; Bellé, Tania R. L.; Rios, Karina R.; Rost, Débora; Tusset, Josiane; Beckert, Fabiele (Salão do Conhecimento, 2013)
Resumo